Modified Korteweg-de Vries hierarchy with hodograph transformation: Camassa-Holm and Harry-Dym hierarchies - Kraenkel, Roberto André [UNESP]; Zenchuk, A. I. (Elsevier B.V., 2001)
In this paper, we present relations between Camassa-Holm (CH), Harry-Dym (HD) and modified Korteweg-de Vries (mKdV) hierarchies, which are given by the hodograph type transformation. (C) 2001 IMACS. Published by Elsevier B.V. B.V. All rights reserved.
Keywords: hierarchies; Harry-Dym hierarchies; Camassa-Holm equation; integrable systems